Penegakan Hukum Internasional terhadap Serangan Siber terhadap Infrastruktur Kritis di Indonesia - Anny Susilowati (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2025)
Cyberattacks on critical infrastructure have become a major challenge in the era of global digitalization. The problem formulation in this study is how international law is applied to address cyberattacks on critical infrastructure in Indonesia, what challenges Indonesia faces in enforcing international law regarding cyberattacks on critical infrastructure, and what efforts are made to overcome these challenges in enforcing international law related to cyberattacks on critical infrastructure in Indonesia. The research method used in this study is normative legal research. The research results show that the enforcement of international law against cyberattacks on critical infrastructure in Indonesia faces significant challenges, such as unclear regulations, issues of state sovereignty, and disagreements between countries. Although Indonesia has participated in international initiatives such as the Budapest Convention and UNGGE, the international law enforcement mechanism is still ineffective in addressing cross-border cyberattacks. Indonesia's domestic law, such as the ITE Law, is still limited in dealing with threats from abroad. Therefore, closer international cooperation, updating domestic policies, and strengthening domestic legal and technological capacities are necessary to ensure more effective and responsive protection against cyber threats.